trans-1,4-dibromocyclohexane-1,4-dicarboxylic acid - Echeverría, Gustavo Alberto (2003)
Molecules of the title compound, C8H10Br2O4, located on symmetry centers, are in a rigid chair conformation, with the COOH and Br substituents axial and equatorial, respectively. The carboxylic acid groups form hydrogen bonds, in a cyclic motif, leading to infinite chains along the b axis.